Water Allocation Efforts with Water Balance Analysis in the Jatiroto Sub-Watershed and Asem Sub Watershed, Lumajang Districts - Prihantono, Gunawan Eko; Halik, Gusfan; Hidayah, Entin (Universitas Jember, 2021)
Currently, water demand is increasing, both domestic, industrial and agricultural water needs. However, the increase in water demand is not due to an increase in the water availability due to changes in land use and other factors that pose a threat to increased exploitation of water resources. So it is necessary to analyze and evaluate the water needs to anticipate the impact of drought in the Asem-Tekung-Jatirowo sub watersheds. The calculation of water supply and water demand can be carried out using the water balance method, assisted by the WEAP (Evaporation and Water Planning) program, through data integration of streamflow analysis and water user in the river reach. The results showed that the sub-watershed area showed a deficit of water in 2013, with the Jatiroto region having the highest air deficit of 1.58 million m3 or 44.2%. Based on this analysis, urgently needed a recommendation of drought anticipation strategies these are planting patterns to adjust condition of water supply, storage of water reserves, conservation of critical land, and repair of channels that are at risk of water seepage.